The Roles of Corticotropin Releasing Factor (CRF) in Responses to Emotional Stress: Is CRF Release a Cause or Result of Fear/Anxiety? - Ohmura, Yu; Yoshioka, Mitsuhiro (CNS & Neurological Disorders - Drug Targets, 2009)
Corticotropin releasing factor (CRF) is a neuropeptide that is a major regulator of the hypothalamic-pituitaryadrenal system. Recent findings have shown that CRF exists in extrahypothalamic areas in the brain as well as in the hypothalamus, and extrahypothalamic CRF is also deeply involved in stress responses. Therefore, CRF has been a major target of drug development for treatment of stress-related disorders. However, whether CRF is a cause or a result of fear/anxiety has not been investigated extensively, even though this issue is extremely important to the development of treatments for stress-related disorders. This article aims to 1) introduce readers to several functional aspects of CRF, focusing on aspects that have been missed or ignored when determining the roles of CRF in responses to emotional stress; 2) critically review previous studies regarding the roles of CRF in responses to emotional stress, considering functional aspects of CRF described in 1); and 3) put forward a hypothesis about the roles of CRF in stress responses. Considering different functional aspects of CRF, it is suggested that CRF is a result of fear/anxiety, rather than a cause. In other words, CRF could be responsible for stress responses to cope with dangerous situations but not for fear/anxiety itself. CRF as a potential target of drug development for treatment of stress-related disorders is also discussed.
Keywords: corticotropin releasing hormone